2003
DOI: 10.1103/physreve.68.067102
|View full text |Cite
|
Sign up to set email alerts
|

Universality of anomalous one-dimensional heat conductivity

Abstract: In one and two dimensions, transport coefficients may diverge in the thermodynamic limit due to long-time correlation of the corresponding currents. The effective asymptotic behaviour is addressed with reference to the problem of heat transport in 1d crystals, modeled by chains of classical nonlinear oscillators. Extensive accurate equilibrium and nonequilibrium numerical simulations confirm that the finite-size thermal conductivity diverges with the system size L as κ ∝ L α . However, the exponent α deviates … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

42
900
5
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 450 publications
(949 citation statements)
references
References 20 publications
42
900
5
2
Order By: Relevance
“…Theoretical predictions that the intrinsic thermal conductivity K -limited by the crystal anharmonicy alone -can diverge with the crystal size L in 2D and 1D systems, continue to ignite debates [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]. Theoretical studies of the lattice thermal transport in 2D anharmonic Fermi-Pasta-Ulam (FPU) lattices [2][3], 2D…”
Section: Context Imagementioning
confidence: 99%
See 2 more Smart Citations
“…Theoretical predictions that the intrinsic thermal conductivity K -limited by the crystal anharmonicy alone -can diverge with the crystal size L in 2D and 1D systems, continue to ignite debates [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]. Theoretical studies of the lattice thermal transport in 2D anharmonic Fermi-Pasta-Ulam (FPU) lattices [2][3], 2D…”
Section: Context Imagementioning
confidence: 99%
“…anharmonic Lennard-Jones lattices [3], 2D harmonic lattices with disorder [4] and 1D FPU chains [2][3]5] suggested that the lattice, i.e. phonon, thermal conductivity K diverges as log(L) for 2D lattices and as L  for 1D chains (<1), where the length L is proportional to the number of the lattice points N along the heat propagation direction [2][3][4][5].…”
Section: Context Imagementioning
confidence: 99%
See 1 more Smart Citation
“…В частности, даже в одномерном контексте нет строгого вывода закона теплопроводности Фурье, согласно которому поток тепла пропорционален градиенту температуры [1]. Многие работы, почти все с использованием компьютерных вычислений [2] и с результатами, противоречащи-ми другу другу, были посвящены этой теме со времени первых строгих исследо-ваний по гармоническим цепочкам осцилляторов с термостатами на границах [3] -модели, которая не подчиняется закону Фурье. Недавно к гармонической цепочке осцилляторов вернулись в рамках аналитических исследований, но при условии, что каждый узел взаимодействует со стохастическим резервуаром.…”
Section: Introductionunclassified
“…They predicted that the heat flux was proportional to the temperature difference, rather than the temperature gradient, thus showing that homogeneous harmonic chains do not exhibit normal transport properties. Although there are many aspects of linear chains, such as the inclusion of disorder or varying masses [101] that we have not considered above, our main concern here is with nonlinear chains. Numerical studies of heat conductivity in the FPU chain were reconsidered at the end of the 1960s.…”
Section: Heat Transport In Lattice Modelsmentioning
confidence: 99%